Sektor Basis Kabupaten Batang Hari dan Implikasinya terhadap Pertumbuhan Ekonomi dan Penyerapan Tenaga Kerja - Hustia, Anggreany (MOTIVASI, 2017)
ABSTRACT Purpose - The problem of this study was knowing Implications For Sector Base, Absorption Of Labor And Economic Growth, Batang HariDesign/methodology - Location Quotient Method Is Used To Determine Whether The Sector Or Sub-Sector Of The Economy, Including Activities Or Non-Base BasisFindings – The results showed that Sector Base In Batang Haritidak Significant Implications On Economic Growth. Sector Base In Batang Hari Is Not Significant Implications On Employment, But The Implications For The Economy Melaluipertumbuhan Employment That Is Equal To 0.080. Economic Growth Is Not Significant Implications On Employment In Batang Hari.